2021
DOI: 10.1155/2021/8010694
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin Deficiency Suppresses Rhabdomyosarcoma Associated with Gut Microbiota Regulation

Abstract: The gut microbiota is very important in the initiation, progression, and dissemination of cancer, and the regulation of microbiota has been employed as a novel strategy to enhance the effect of immunotherapy. Adiponectin (APN), an adipocyte-derived hormone, plays a vital role in regulating the immune response of innate immune cells. The deficiency of APN inhibits rhabdomyosarcoma growth. However, whether this function is associated with regulating gut microbiota remains unknown. To investigate, we performed 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Meanwhile, previous study revealed that alteration of gut microbiota could affect the expression of APN in obese mice ( Yao et al., 2020 ). The supplementation with APN might have an impact on both the pattern and composition of the gut microbiota ( Grases-Pintó et al., 2019 ), and APN deficiency could alter the gut microbial functions ( Peng et al., 2021 ). Although gut microbiota has been associated with the APN, the role of APN in the gut microbiota-brain axis hypothesis of depression has not been studied to date.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, previous study revealed that alteration of gut microbiota could affect the expression of APN in obese mice ( Yao et al., 2020 ). The supplementation with APN might have an impact on both the pattern and composition of the gut microbiota ( Grases-Pintó et al., 2019 ), and APN deficiency could alter the gut microbial functions ( Peng et al., 2021 ). Although gut microbiota has been associated with the APN, the role of APN in the gut microbiota-brain axis hypothesis of depression has not been studied to date.…”
Section: Discussionmentioning
confidence: 99%
“…The fecal 16S rRNA analysis was performed as previously described [ 73 ]. In brief, total microbial DNA from feces was extracted using the QIAamp DNA Micro Kit (TIANGEN, China).…”
Section: Methodsmentioning
confidence: 99%